Amelioration of aorta morphology in spontaneous hypertensive rat (SHR) by syzygium polyanthum - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam; Baharun, Bibi Nur Bazlini; Ramli, Nurul Syahida; Noordin, Liza (Elsevier, 2018)
Background: Prolonged uncontrolled hypertension can lead to vessels damage; manifested as abnormal morphology changes. Sygyzium polyanthum has been shown to has blood pressure lowering effects in SHR rats. Objective: This study was designed to evaluate the improvement effects of S. polyanthum aqueous leave extracts (AESP) on the descending thoracic aorta morphology damaged secondary to hypertension. Material & Methods: Twenty-one rats were used in this study, with 7 rats in each group. Group 1: normotensive Wistar Kyoto (WKY) rat, Group 2: untreated SHR, Group 3: SHR on AESP (2250 mg/kg). AESP was orally administered daily for 3 months. The descending thoracic aorta was harvested at the end of the study. The aorta morphology was evaluated using Hematoxylin and Eosin stain (H&E stain) and Scanning Electron Microscope (SEM). Systolic blood pressure (SBP) were also recorded every 2 weeks during the study. Results: On HE stained, treatment with AESP increased the endothelial cell lining on the surface of aortic tunica intima. The endothelial lining also notably smoother. The elastic laminae were not discontinued and more regular pattern of vascular smooth muscle cells with elongated nuclei. The thickness ratio of tunica media to tunica intima was also reduced. Under SEM, the surface of the aorta was smoother and there were no crater-like defects as compared to untreated SHR. There were also no inflammatory cells or fibrinogen seen as on the aortic surface of untreated SHR. The SBP in AESP-treated SHR was significantly reduced (107.00 + 1.68 mmHg) as compared to untreated SHR (199.75 + 2.86 mmHg, p<0.001). Conclusion: S. polyanthum improves the morphology of aorta and also significantly reduces the blood pressure.